DEVELOPMENT OF E-BOOK USING BOOK CREATOR TO ENHANCE STUDENTS UNDERSTANDING OF NARRATIVE TEXT ON READING SKILL - Muhammad Farras Fadhil; Siti Niah; Prih Febtiningsih (Jurnal Basataka (JBT), 2025)
This research aims to develop a digital learning medium in the form of an interactive e-book using Book Creator to enhance students’ understanding of narrative texts in English reading skills. The study was conducted at SMP Tuah Negeri Pekanbaru and employed the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The e-book was designed based on curriculum indicators and equipped with multimedia features such as audio narration, videos, illustrations, and interactive quizzes to support student engagement and comprehension. Validation was conducted by content and media experts, yielding a feasibility score of 92%, categorized as "very feasible." The e-book was tested on 26 eighth-grade students using pre-test and post-test instruments to measure its effectiveness. Results indicated a significant improvement in students’ reading comprehension, with 65.4% achieving a high N-Gain score. Students demonstrated better understanding of narrative structures, main ideas, and moral values. Additionally, the e-book increased motivation, facilitated independent learning, and enabled flexible access across devices. Teachers reported positive shifts in classroom dynamics, moving towards a more interactive and student-centered learning environment. The findings support the effectiveness of e-books as instructional media in English as a Foreign Language (EFL) classrooms. It also highlights the potential of localized digital content to enhance learning outcomes in regions with limited access to conventional resources. This study concludes that Book Creator-based e-books can serve as a valuable tool in fostering students’ reading comprehension through engaging, contextually relevant, and accessible digital media.